A Sperm Quality Detection System Based on Microfluidic Chip and Micro-Imaging System - Pan, Xiaoqing; Gao, Kang; Yang, Ning; Wang, Yafei; Zhang, Xiaodong; Shao, Le; Zhai, Pin; Qin, Feng; Zhang, Xia; Li, Jian; Wang, Xinglong; Yang, Jie (Frontiers in Veterinary Science, 2022)
Sperm quality assessment is the main method to predict the reproductive ability of livestock. The detection of livestock’s sperm quality is significant to the application of artificial insemination technology and in-vitro fertilization technology. In order to com-prehensively estimate the sperm quality and improve the real-time capability and portability of sperm quality detection, this paper develops a portable micro-imaging system based on microfluidic chip. The system realizes the comprehensive estimation of sperm quality through the detection of sperm motility and survival rate. In terms of hardware, a microfluidic chip that can automatically mix samples is designed. An optical system with a magnification of 400 is developed for sperm microscopic observation. In terms of software, a set of algorithms for identifying sperm motility and survival rate is proposed for the comprehensive estimation of sperm quality, based on OpenCV. The system’s detection accuracy of the sperm survival rate is 94.0%, while the error rate is 0.6%; the sperm motility estimation results are consistent with the those of Computer Assisted Sperm Analysis (CASA); and the recogni-tion time of the system is 9 seconds, this system is suitable for rapid detection of sperm quality in livestock.